Proof Of Financial Loss State of Financial Audit Audit Results Against Action Criminal Corruption - Rahmayanti (International Journal of Society and Law, 2024)
Loss finance country in Constitution Act Criminal Corruption This is something that must be fulfilled in order to recover financial compensation country. The Corruption Eradication Law provides options related enforcement case corruption Which consists from dropping criminal And recovery of state losses through additional criminal penalties and civil lawsuits, will but considering the impact caused by criminal acts of corruption influence on state finances, it is appropriate for enforcement officers law more put forward effort return loss country compared with imprisonment. The problem formulation in this research consists of: proving financial losses country from results auditing body inspection finance (CPC) in follow criminal corruption. The type of research used in this research is juridical research normative, As for characteristic study Which used in study This nature literature, while research data was obtained from legal norms there is in regulation legislation (library research). The State Financial Audit Agency (BPK) is very important as it has been explained in the first discussion, namely the State financial audit agency In its implementation, the BPK is based on the importance of the audit function and supervision in state administration. The existence of the body that will be carrying out audit functions has been included in the Constitution stated that For inspect not quite enough answer about finance country held a Financial Audit Agency, whose regulations are determined by Law Invite (Chapter 23 Chapter VIII Constitution 1945). Disobedient to provision legislation, as well as findings imprudence; inefficiency; And ineffectiveness. Non-compliance with statutory provisions consists of findings that have a financial impact, namely losses, potential losses and deficiencies reception.